Caractériser les problèmes des élèves avec le savoir pour comprendre l'espace de décisions du professeur dans le contexte d’un enseignement des nombres et de leurs usages - Serge Quilio (Recherches en Éducation)
In this article we implement a form of didactic analysis, the bottom-up analysis of the transposition and the a priori analysis of the situation, in the particular context of a cooperative didactic engineering in which researchers and teachers cooperate in the development, implementation and collective analysis of primary school mathematics education. We show by means of episodes observed in class how the development of this type of analysis can give access to the meaning of the practices for the students but also their meaning for the teachers. We claim that the bottom up analysis of the didactic transposition provides an insight on the decisions that the teacher may take to set up alternative teaching paths